Preventing and protecting against underwater cultural heritage crime - Looram, Charlotte Papillaud; Lindley, Jade (Frontiers in Conservation Science, 2024)
Akin to the activity on the high seas broadly, underwater cultural heritage below the surface of the high seas is beyond the scope of policing of any one state. As such, the historical, cultural, and financial value of shipwrecks are vulnerable to crimes such as looting, trafficking, forgeries and then, illicit sales, rather than providing cultural benefit to all, as articulated in the 1982 United Nations Convention on the Law of the Sea and the 2001 Conven7on on the Protec7on of the Underwater Cultural Heritage. The emergent United Nations High Seas Treaty provides some hope of unclouding this complex space and providing protections for these culturally rich, priceless, and often nationally contested objects. Shipwreck ownership is contested not only on the high seas. Shipwrecks found within a state's exclusive economic zone may be susceptible to questions of ownership, further challenging the questions of how crimes against underwater cultural heritage can be collectively prevented and protected. Drawing on a shipwreck example from Southeast Asia in which ownership was contested, the Geldermalsen, this article considers, within the framework of international law and increasingly available technology, it may be possible to 'design out' criminal vulnerabilities through a lens of situational crime prevention.